1999
DOI: 10.1161/01.hyp.33.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Role of C/A Polymorphism at −20 on the Expression of Human Angiotensinogen Gene

Abstract: Abstract-Angiotensinogen is the glycoprotein precursor of 1 of the most potent vasoactive hormones, angiotensin II.Human angiotensinogen gene contains a C/A polymorphism at Ϫ20 located between the TATA box and transcriptional initiation site. We show here that when nucleoside A is present at Ϫ20, this sequence binds to the estrogen receptor.We also show that transcriptional activity of reporter constructs containing human angiotensinogen gene promoter with nucleoside A at Ϫ20 is increased on cotransfection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 20 publications
6
73
0
Order By: Relevance
“…It has been previously demonstrated that the C allele of the AGT A-20C gene polymorphism (rs5050) is associated with an increased AGT production according to genotype (AA < AC < CC) and its plasmatic concentration is progressively higher [14]. Recent studies in this respect started with the observation that co-treatments with ARB are correlated with a decreased number of ulcer in patients treated with LDA [15].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that the C allele of the AGT A-20C gene polymorphism (rs5050) is associated with an increased AGT production according to genotype (AA < AC < CC) and its plasmatic concentration is progressively higher [14]. Recent studies in this respect started with the observation that co-treatments with ARB are correlated with a decreased number of ulcer in patients treated with LDA [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, among them, only a small number have been shown to possess functional EREs within the transcription regulatory region. In mammals, these genes include transcription factors, such as JUN [32] , FOS [33] , PGR [34] , and TP53 [35] , intracellular signaling molecules, such as HRAS [36] , BCL2 [37] , and BRCA1 [38] , enzymes, such as CHAT [39] , NQO1 [40] , and CKB [41] , secreted proteins, such as LTF [42] , SCGB1A1 [43] , OVGP1 [44] , C3 [45] , and AGT [46] , hormones, such as LHB [47] , OXT [48] , PRL [49] , and AVP [50] , membrane proteins, such as SNAT2 [51] and VEGFA [52] , the motogen TFF1 [53] , and the protease CTSD [54] . These genes are assumed to directly mediate various estrogen actions in normal tissues, as well as in cancer and other diseases.…”
Section: Steroid Hormone Target Genes and The Transcription Cascadementioning
confidence: 99%
“…Many additional polymorphisms, however, have been identified in the AGT gene, including an additional promoter polymorphism at −20. This polymorphism is also interesting, since depending on the genotype different response elements are generated, including those for estrogen receptor α, upstream regulatory factor and members of the COUP-TF family, which correlates with different phenotypes, including pregnancydependent variations in AGT levels, non-modulating hypertension and an altered relationship between BMI and blood pressure (Zhao et al 1999;Morgan et al 2000;Hilgers et al 2001;Tiago et al 2002). Current research efforts address the haplotype structure of the AGT gene, which should be comparatively easy given the short length of the gene of only ∼12 kb.…”
Section: Polymorphisms In the Angiotensinogen Genementioning
confidence: 99%